Morgagni-Larrey parasternal diaphragmatic hernia masquerading as pleural effusion: an interesting presentation with review of literature - Gupta, Amit; Singh, Sudhir Kumar; Darbari, Anshuman; S., Durga Sowmya; Mani, Rishit (International Surgery Journal, 2020)
Congenital diaphragmatic hernia (CDH) is a major malformation found in newborns and babies but rarely in adults. CDH is defined by the presence of a defect in the diaphragm, which permits the herniation of abdominal contents into the thorax. The diagnosis of CDH is based on clinical history, examinations and is confirmed by plain X-ray films and computed tomography scans. Here we report a case which was misdiagnosed at another centre as pleural effusion and managed by placement of intercostal tube drainage and later on diagnosed to be case of Morgnani-Larrey parasternal diaphragmatic hernia. Congenital diaphragmatic hernia (CDH) is a major malformation found in newborns and babies but rarely in adults. CDH is defined by the presence of a defect in the diaphragm, which permits the herniation of abdominal contents into the thorax. The diagnosis of CDH is based on clinical history, examinations and is confirmed by plain X-ray films and computed tomography scans. The purpose of reporting this case is to provide information on late-presenting CDH and to emphasize that a high index of suspicion is required for diagnosis and to avoid unwanted complications.